2017
DOI: 10.1111/imig.12347
|View full text |Cite
|
Sign up to set email alerts
|

Decision to Emigrate amongst the Youth in Lebanon

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 41 publications
(53 reference statements)
8
24
0
1
Order By: Relevance
“…They conceptualized this as a form of ‘lifestyle migration’ as the result of a search for ‘self-fulfillment’ [12,13]. Studies on migrants in Middle Eastern and North Africa countries have found that young people from non-wealthy backgrounds and unemployed are more likely to emigrate, and self-select along the cultural traits of religiosity and gender-egalitarian [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…They conceptualized this as a form of ‘lifestyle migration’ as the result of a search for ‘self-fulfillment’ [12,13]. Studies on migrants in Middle Eastern and North Africa countries have found that young people from non-wealthy backgrounds and unemployed are more likely to emigrate, and self-select along the cultural traits of religiosity and gender-egalitarian [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The very extensive research into youth migration out of developing countries includes the cases of Ecuador, Mexico and Peru (Cazzuffi & Fernández, 2018), The Philippines (Manalo IV & van de Fliert, 2013) and Lebanon (Dibeh, Fakih & Marrouch, 2017). What are mostly explored in these cases are the reasons for young people to move out of rural townships, with further consideration given to benefits and costs for both migrants and the rural areas affected, as well as the factors stimulating young people to either return to or stay in a given region.…”
Section: Axes To the Empirical Research Being Carried Out On Youth Oumentioning
confidence: 99%
“…Youth emigration intentions are also widely analyzed in the international context: (Dako-Gyeke, 2016) explored the migration intentions of Ghanaian youth and conducted a qualitative study to find out what motives motivate young people to emigrate; Roman and Vasilescu (2016) as well aimed to determine the factors that influence the decision of youth to migrate (Romanian youth case), one of the research results was that discrimination and the entrepreneurial behaviour were key factors that influenced the migration intentions of young adults, etc. There are even more authors who analyzed youth emigration, mentioning some of the newest: (Chuvashov, 2014;van Mol, 2016;Dibeh, Fakih, & Marrouch, 2018;Salamonska & Czeranowska, 2018;Traikova, Mollers, & Petrick, 2018;Bastianon, 2019;Bakina, Yaremtchuk, Orlova, & Krasnoperova, 2019;Herz, Diaz-Chorne, Diaz-Catalan, Altissimo, & Carignani, 2019, etc. ).…”
Section: Introductionmentioning
confidence: 99%